Democratic Transition and the Rise of Populist Majoritarianism Constitutional Reform in Greece and Turkey - Grigoriadis, Ioannis N. (Reform and Transition in the Mediterranean, 2018)
This comparative study explores the impact of populist majoritarianism on Greek and Turkish democratic transition. Using the case studies of Greece and Turkey, the author argues that while majoritarianism is often celebrated as a manifestation of popular sovereignty, it can undermine institutional performance. In cases of transition states where social capital is scarce and polarization is high, it can even upset the process of democratic consolidation, contributing to a confrontational and inefficient democratic regime. A "mild democracy" would require a calibrated system of checks and balances, trust- and consensus-building mechanisms. This book will be of use to students and scholars interested in the fields of Greek and Turkish politics, law and democratization.